Cleft lip/palate and CDH1/E-cadherin mutations in families with hereditary diffuse gastric cancer. Issue 2 (14th April 2005) - Frebourg, T; Oliveira, C; Hochain, P; Karam, R; Manouvrier, S; Graziadio, C; Vekemans, M; Hartmann, A; Baert-Desurmont, S; Alexandre, C; Lejeune Dumoulin, S; Marroni, C; et al.
Abstract : We report the association of CDH1/E-cadherin mutations with cleft lip, with or without cleft palate (CLP), in two families with hereditary diffuse gastric cancer (HDGC). In each family, the CDH1 mutation was a splicing mutation generating aberrant transcripts with an in-frame deletion, removing the extracellular cadherin repeat domains involved in cell-cell adhesion. Such transcripts might encode mutant proteins with trans-dominant negative effects. We found that CDH1 is highly expressed at 4 and 5 weeks in the frontonasal prominence, and at 6 weeks in the lateral and medial nasal prominences of human embryos, and is therefore expressed during the critical stages of lip and palate development. These findings suggest that alteration of the E-cadherin pathway can contribute to human clefting.